PEMBIASAAN KARAKTER DISIPLIN MELALUI OPENING PAGI DALAM MEWUJUDKAN AKHLAKUL KARIMAH DI SEKOLAH (Studi di Kelas VI Sekolah Dasar Alam Insan Cemerlang Kabupaten Bandung) - nanang Abdulhaq (ASWAJA: Jurnal Pendidikan dan Keislaman, 2021)
Nanang Abdul Haq. Discipline Character Habituation Through Morning Opening in Realizing Akhlakul Karimah in Schools (Study in Grade VI  Alam Insan Cemerlang Elementary School, Bandung Regency). This research was conducted against the background of the negative influence of the current of globalization which makes humans characterless (good-weak, bad-strong, bad-weak characters). Departing from this problem, there needs to be habituation and example in shaping character. And exemplary plays a major role in realizing a moral revolution and spiritual character in the world of education and presenting all believing Muslims how to act and behave so as not to fall into negative actions that are very worrying. FromFor the above reasons, researchers are interested in researching habituation-based character formation at the Alam Insan Cemerlang Elementary School because this school has seen its success in shaping the character of its students. The purpose of this study, first, is to find out, explain the purpose of characterizing students' character through Opening mornings at Alam Insan Cemerlang Elementary School. Second, to find out and explain the character formation of students based on discipline habituation through the Morning Opening. Third, to find out the success of character building based on habituation of discipline through the Morning Opening at the Alam Insan Cemerlang Elementary School. Fourth, to find out the supporters and obstacles to habituation of disciplined characters in SD Alam Insan Cemerlang. This research is a qualitative descriptive with a phenomenological approach, so in collecting data, the authors use observation techniques, in-depth interviews, documentation  and data analysis techniques. The results showed that the formation of character based on habituation of disciplined character through opening morning at SD Alam Insan Cemerlang was carried out with various activities, namely: (1) praying together in the morning, (2) reading Al-Quran literacy, (3) praying Duha, (4) garbage collection activities, (GPS) (5) Friday donation activities. The implementation of exemplary-based character consists of: (1) through motivational encouragement, (2) providing understanding, (3) giving advice, (4) giving sanctions, (5) being an example for students, (6) giving gifts. The success of character building based on habituation and exemplary that can give birth to characters, such as: (1 ) religious values, (2) discipline values, (3) moral values. Supporting factors (1) maximum service (2) exemplary principals and teachers (3) adequate infrastructure (4) support from parents (5) program consistency. The obstacles are (1) the family environment (2) the community environment (3) students and perceptions of disciplined culture.